Estramustine Phosphate Inhibits TGF-β-Induced Mouse Macrophage Migration and Urokinase-Type Plasminogen Activator Production. (2nd September 2018) - Mojsilovic, Sonja S.; Mojsilovic, Slavko; Bjelica, Suncica; Santibanez, Juan F.
Abstract : Transforming growth factor-beta (TGF- β ) has been demonstrated as a key regulator of immune responses including monocyte/macrophage functions. TGF- β regulates macrophage cell migration and polarization, as well as it is shown to modulate macrophage urokinase-type plasminogen activator (uPA) production, which also contributes to macrophage chemotaxis and migration toward damaged or inflamed tissues. Microtubule (MT) cytoskeleton dynamic plays a key role during the cell motility, and any interference on the MT network profoundly affects cell migration. In this study, by using estramustine phosphate (EP), which modifies MT stability, we analysed whether tubulin cytoskeleton contributes to TGF- β -induced macrophage cell migration and uPA expression. We found out that, in the murine macrophage cell line RAW 264.7, EP at noncytotoxic concentrations inhibited cell migration and uPA expression induced by TGF- β . Moreover, EP greatly reduced the capacity of TGF- β to trigger the phosphorylation and activation of its downstream Smad3 effector. Furthermore, Smad3 activation seems to be critical for the increased cell motility. Thus, our data suggest that EP, by interfering with MT dynamics, inhibits TGF- β -induced RAW 264.7 cell migration paralleled with reduction of uPA induction, in part by disabling Smad3 activation by TGF- β .